Early diagnosis of diaphragm palsy after pediatric cardiac surgery and outcome after diaphragm plication - A single-center experience - Divyakant Parmar; Jigar Panchal; Neha Parmar; Pankaj Garg; Amit Mishra; Jigar Surti; Kartik Patel (Wolters Kluwer Medknow Publications, 2021)
Objective : The aims of our prospective observational study were to evaluate the (1) reliability of clinical signs in the early detection of diaphragm palsy (DP); (2) reliability of ultrasonography using echo machine as a bedside tool for the diagnosis of DP; and (3) does early diaphragm plication result in the improved outcome? We also sought to determine the incidence and predominant risk factors for DP and diaphragm plication at our center. Materials and Methods : This prospective observational study included patients with suspected DP from January 2015 to December 2018. Patients with suspected DP were initially evaluated by bedside ultrasonography using echo machine and confirmed by fluoroscopy. Diaphragm plication was considered for patients having respiratory distress, difficult weaning, or failed extubation attempt without any obvious cardiac or pulmonary etiology. Patients were followed for 3 months after discharge to assess diaphragm function. Results : A total of 87 patients were suspected of DP based on clinical signs. DP was diagnosed in 61 patients on fluoroscopy. The median time from index operation to diagnosis was 10 (1-59) days. Diaphragm plication was done among 52 patients and not done in nine patients. Bedside ultrasonography using echo machine was 96.7% sensitive and 96.15% specific in diagnosing DP. Early plication (< 14 days) significantly reduced the need for nasal continuous positive airway pressure (65% vs. 96%, P = 0.02), duration of mechanical ventilation (12 vs. 25 days, P = 0.018), intensive care unit (ICU) stay (25 days vs. 39 days, P = 0.019), and hospital stay (30 days vs. 46 days, P = 0.036). Conclusion : Hoover's sign and raised hemidiaphragm on chest X-ray are the most specific clinical signs to suspect unilateral DP. Bedside ultrasonography using an echo machine is a good diagnostic investigation comparable to fluoroscopy. Early plication facilitates weaning from the ventilator and thereby decreases the ICU stay and hospital stay.